The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1007/bf00009597
|View full text |Cite
|
Sign up to set email alerts
|

A revision of Dasyrhynchus Pintner (Cestoda: Trypanorhyncha), parasitic in elasmobranch and teleost fishes

Abstract: The genus Dasyrhynchus Pintner is revised. The adult of D. pacificus Robinson,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
2
7
0
1
Order By: Relevance
“…A similar shift in orientation, but from internal-external to bothrial-antibothrial has been reported in the eutetrarhynchoid genus Hemionchos Campbell et Beveridge, 2006 from species of Mobula from the Gulf of California, Mexico (Campbell and Beveridge 2006). Although not described as such, examination of illustrations of Dasyrhynchus pacificus Robinson, 1959 (see Beveridge andCampbell 1993, fig. 3) and D. talismani Dollfus, 1935 (see Beveridge andCampbell 1993, fig.…”
Section: Discussionsupporting
confidence: 56%
“…A similar shift in orientation, but from internal-external to bothrial-antibothrial has been reported in the eutetrarhynchoid genus Hemionchos Campbell et Beveridge, 2006 from species of Mobula from the Gulf of California, Mexico (Campbell and Beveridge 2006). Although not described as such, examination of illustrations of Dasyrhynchus pacificus Robinson, 1959 (see Beveridge andCampbell 1993, fig. 3) and D. talismani Dollfus, 1935 (see Beveridge andCampbell 1993, fig.…”
Section: Discussionsupporting
confidence: 56%
“…• Otobothrium cysticum (Mayer, 1842) (Beveridge and Campbell 1993). This is its first record from the Gulf of Mexico, but the identification should be corroborated with adult material.…”
Section: Remarksmentioning
confidence: 98%
“…The latter three species also either already have been reported from or are expected to occur in the Gulf of Mexico. However, the specimens from Hawaii reported as D. giganteus were immature and when re-examined by Beveridge and Campbell (1993), the authors suggested the specimens were D. variouncinatus (Pintner, 1913) because a mature specimen of that species occurred in Carcharhinus falciformis (Bibron) (silky shark) off Hawaii. All records of D. variouncinatus from the Atlantic Ocean (see Dollfus 1969) were considered by Beveridge and Campbell (1993) to represent D. giganteus.…”
Section: Other Adult Trypanorhynchsmentioning
confidence: 99%
“…Five other specimens examined during the main investigation with a total size of 14-35 cm were not infested (Table). Beveridge and Campbell (1993) stated that it is not possible to separate D. giganteus from the related D. variouncinatus only on the basis of the hooklet arrangement. Examination of segment anatomy of adult worms is necessary to differentiate the species.…”
Section: Nybelinia Senegalensismentioning
confidence: 99%
“…Examination of segment anatomy of adult worms is necessary to differentiate the species. However, currently all specimens found in the Atlantic Ocean with a hooklet arrangement typical for these two species are considered as belonging to D. giganteus (Beveridge & Campbell 1993). This species was originally described from Brazil and has a transoceanic distribution in the tropical part of the Atlantic.…”
Section: Nybelinia Senegalensismentioning
confidence: 99%